Reconstructing the Concept of Halal Product Guarantee in Realizing Justice and Benefit - Hamid, Abdul; Diniyanto, Ayon; Holish, Amaru Muftie (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2023)
Halal product assurance in Indonesia presents challenges requiring correction, particularly concerning (1) conception, (2) implementation, and (3) reconstruction of halal product guarantees. The current concept results in a passive government, dependent on public initiatives. Reconstruction is essential to highlight the active governmental role and reinforce societal engagement. This research formulates the halal product guarantee concept, assesses its Indonesian implementation, and proposes reconstruction for justice and benefit. Employing doctrinal research methods, the study analyses legislation, concepts, history, and cases, utilizing primary and secondary legal materials with documentation as the primary data collection technique. Findings reveal the current halal product assurance concept renders the government passive, prompting a public call for its active involvement. Reconstruction becomes pivotal to prevent controversies. The revamped concept should focus on enhancing community involvement and ensuring an active government role. Community engagement with a uniform understanding is crucial, and the government should actively participate, including empowering investigations. This study contributes conceptual insights, urging an evaluation and reformulation of halal product guarantees, emphasizing the active state role through the government. The recommendations aim to improve the conception of halal product guarantees and foster a more active, inclusive approach to ensure justice and societal well-being.